A valid and applicable measurement method for knowledge worker productivity - Heidary Dahooie, Jalil; Ghezel Arsalan, Mohammad Reza; Zolghadr Shojai, Ali (International journal of productivity and performance management, 2018)
Purpose The purpose of this paper is to propose a new method for knowledge worker productivity measurement which is based on valid principles and appropriate viewpoints. Design/methodology/approach Based on an extensive and thorough literature review the elements that need to be taken into consideration, while designing a method for knowledge worker productivity measurement, are determined and divided into principles and viewpoints. These elements must be incorporated into the design of knowledge worker productivity measurement methods so that the correctness and accuracy of these methods can be verified. The proposed model, which is based on appropriate principles and viewpoints, determines the outputs of knowledge work with respect to the tasks that a worker’s job includes. Considering nine measures, these outputs are evaluated using fuzzy numbers and, then, quantified. The inputs of knowledge work are knowledge, skills and abilities (KSAs) required to do the job. These inputs are identified and quantified using Job Element Method. Furthermore, fuzzy Data Envelopment Analysis is employed to model the productivity. Findings In this paper, the proposed method for knowledge worker productivity measurement follows both appropriate principles and viewpoints, simultaneously. In order to validate the obtained results and explore the applicability of the proposed method, a case study was carried out at an Iranian organization in electric power industry. Statistical analyses are employed to prove the validity of the results. Based on the obtained results, the productivity of a knowledge worker is said to be high when he/she delivers the expected amount of job outputs considering the values of his/her inputs (KSAs). Originality/value The originality of this paper is twofold. First, the extracted principles and viewpoints can serve as a guideline for the development of similar methods. Second, the proposed model offers an effective and efficient tool that can serve as the basis for the comparison among relative productivity of knowledge workers. Furthermore, the obtained results could form a basis to examine the productivity trend of each knowledge worker over different periods of time.